Home or abroad? Exploring medical students' attitudes towards studying and working overseas - Saw Ohn Mar; Fatehpal Singh Malhi; Hakim Gharib Bilal; Syed Rahim Syed Hamid; Osman Ali (Zanjan University of Medical Sciences and Health Services, 2024)
Background & Objective: Cross-border medical student mobility and doctor migration have become global trends. The aim of this study was to explore Malaysian medical students' attitudes towards studying and working overseas. Materials & Methods: A cross-sectional study was conducted among medical students of the academic year 2018-2019 from University Kuala Lumpur, Royal College of Medicine Perak, using a self-administered validated questionnaire that explored their opinions related to encouraging and deterring factors of studying and working overseas and their preferred destination for migration. All 569 students from years 1 to 5 were invited, and 505 completed responses were analyzed. Results: Financial factors were rated as most relevant for not studying overseas by 81.6% of the respondents, whereas language barriers and racial discrimination were considered less relevant. Doing electives overseas was favored by 68.9%. Regarding the benefits of further study abroad, learning international standards and experiencing diversity are rated as "very important" by 75.4% and 62.7%, respectively. They rated better earning (63.2%) and further learning (30.7%) as the most relevant reasons for doctors working overseas, and family commitment (49.9%), Medical Licensing Examinations (MLE) (38.4%), and loyalty to their home country (34.7%) for not working overseas. Their most preferred foreign destinations for further study and working are the UK, Ireland, and Australia. Conclusion: While appreciating the advantages of further study abroad, MLE was considered one of the deterring factors. As a result, consideration should be given to making changes to existing curricula to align with the expected standards of the destined countries